COMPARISON OF SINGLE STAGE VS MULTI STAGE INCUBATION SYSTEMS ON PERFORMANCE OF HATCHING EGGS OF BROILER BREEDERS OF THREE AGES - Maekawa M., Daniel (2014)
The aim of the present study was to compare the productive performance of single stage versus multiple stage incubation in eggs of broiler breeders of three age groups. In the incubation process was used 21 878 026 eggs from Cobb 500 broiler breeders (slow feather) grouped in three age categories: young (24 to 35 weeks), adults (36 to 50 weeks), and old (51 to 63 weeks) for a period of one year. The results showed lower total embryonic mortality in the single stage as compared to the multi stage incubation system (p<0.05), both in the young (9.55 vs 10.49%), adult (7.06 vs 9.62%) and old breeders (8.31 vs 12.55%) as well as higher total hatchability and hatchability of fertile eggs in the single stage incubation system in the three age groups (p<0.05). In addition, it was found a better utilization of the older breeders under the single stage incubation system.